Conceptual viewpoint on the needs for creating green human resource management practices awareness of hotel industry in Nigeria; issues and challenges - Emmanuel, Adeyefa Adedayo; Mansor, Zuraina; Mohd Rasdi, Roziah; Abdullah, Abdul Rashid (Globeedu Group, 2020)
Green practices have in recent years created much attention from academia and practitioners in every part of the world. However, an extensive analysis of green or environmental HRM has not been made so far. To close this gap, the present study provides a thorough literature review that was neglected by researchers in management in the hotel sector in Nigeria and therefore less researched. The purpose of this narrative review paper is to create awareness on the effect of Green practices and Green Human Resource Management strategies with respect to Nigeria Hotels. In addition, the government should adopt policies to encourage the above activities because improving organizational quality will be a positive long-term reflection of the economy. All of these can be achieved through the productive organizational and national human resource development program.